2020
DOI: 10.31393/morphology-journal-2020-26(2)-08
|View full text |Cite
|
Sign up to set email alerts
|

Features correlations of the sizes of molars with cephalometric indicators of men of the western region of Ukraine

Abstract: Expanding the theoretical knowledge of medical anthropology in the modern field of dental services is one of the main drivers of progress in the orthodontic field. The only way to successfully develop the relationship of these disciplines is to create and fill a database of normative data and search for correlations between various, both obviously related and, at first glance, completely unrelated structures of the human body. The purpose of the study was to determine the features of the relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…For residents of western Ukraine, the existence of reliable correlations of medium strength between the linear dimensions of molars (parietal-lingual and mesio-distal dimensions) and indicators of the skull. With the indicators of the facial skull, the largest number of reliable and medium correlations with the height of teeth, crowns, root length, parietal-lingual and mesio-distal dimensions of molars [12]. A similar study, however, conducted with the population of southern Ukraine, found correlations between most sizes of molars on the lower jaw and the length and height of the nose [24].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…For residents of western Ukraine, the existence of reliable correlations of medium strength between the linear dimensions of molars (parietal-lingual and mesio-distal dimensions) and indicators of the skull. With the indicators of the facial skull, the largest number of reliable and medium correlations with the height of teeth, crowns, root length, parietal-lingual and mesio-distal dimensions of molars [12]. A similar study, however, conducted with the population of southern Ukraine, found correlations between most sizes of molars on the lower jaw and the length and height of the nose [24].…”
Section: Introductionmentioning
confidence: 89%
“…Estimated indicators are calculated on the basis of those shown in Figure 2: N-S:S-Ar' -the ratio of the distances S-Ar' (12) and N-S (2) in the cephalometric analysis of Bjork; S-ar:ar-Go -ratio of the distances S-Ar (5) and Ar-Go (7) in the Roth-Jarabak cephalometric analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For residents of Western Ukraine, the largest number of significant correlations between molar size and cranial parameters were found with vestibular-lingual and mesiodistal tooth sizes, and for the facial skull with the height and length of the tooth root [12]. While for the inhabitants of Southern Ukraine the corresponding correlations were found with cranial indicators for tooth height and length of their roots, and for facial skull -with tooth height, root length, vestibular-lingual and mesio-distal dimensions [23].…”
Section: Introductionmentioning
confidence: 98%
“…Data from both domestic and foreign researchers indicate a striking variability of the dental-maxillary system depending on many factors: sex [9], ethnicity [1], facial features [15,20], jaw position [14], regional affiliation [12], features of the structure of the cerebral part of the skull [4], etc. Thus, Ukrainian researchers in the analysis of teleradiograms of Ukrainian boys and girls by the Steiner method established the relationship of the ANB angle with linear (distance 1u_NA) and angular (angles Max1_NA and Max1_SN) characteristics of the upper central incisors and the angle of the lower central incisors (Mand1_NB) [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of studies conducted by domestic researchers have shown that the methods of cephalometric analysis require adaptation for the Ukrainian population considering regional affiliation, gender and age [11,14,21,27].…”
Section: Introductionmentioning
confidence: 99%